Structural characterization of novel chemotactic and mastoparan peptides from the venom of the social wasp Agelaia pallipes pallipes by high-performance liquid chromatography/electrospray ionization tandem mass spectrometry - Mendes, Maria Anita [UNESP]; Souza, Bibiana Monson de [UNESP]; Santos, Lucilene Delazari dos [UNESP]; Palma, Mario Sergio [UNESP] (Wiley-Blackwell, 2004)
High-performance liquid chromatography/electrospray ionization mass spectrometry (HPLC/ESI-MS) and high-performance liquid chromatography/electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) techniques were applied for the detection, purification, monitoring, and sequencing of two novel and biologically active peptides occurring at very low levels in the venom of the wasp Agelaia pallipes pallipes. These peptides were sequenced under LC/ESI-MS/MS conditions and designated as Agelaia-CP (I/L-L-G-T-I-L-G-L-L-K-G-I/L-NH2, MW 1207.8Da) and Agelaia-MP (I/L-N-W-L-K-L-G-K-A-I-I-D-A-I/L-NH2, MW 1565.0Da). The peptide Agelaia-CP showed no hemolytic activity, but it behaved as a mast cell degranulator and induced a potent chemotaxis in polymorphonucleated leukocyte (PMNL) cells, typical of a wasp chemotactic peptide. The peptide Agelaia-MP showed both powerful mast cell degranulation and hemolysis of washed rat red blood cells, and is thus assigned as a new member of the mastoparan family of peptides. Both peptides seem to be directly involved in the strong inflammatory reactions associated with wasp stings. © Copyright 2004 John Wiley & Sons, Ltd.
Keywords: Chemotactic peptide; Mastoparan; Unclassified drug; Wasp venom; Agelaia pallipes pallipes; Animal cell; Bee sting; Electrospray mass spectrometry; Hemolysis; High performance liquid chromatography; Inflammation; Mast cell degranulation; Neutrophil chemotaxis; Nonhuman; Protein analysis; Pprotein purification; Protein structure; Rat; Sequence analysis; Tandem mass spectrometry; Wasp; Wasp sting; Animals; Chemotactic Factors; Chromatography, High Pressure Liquid; Molecular Structure; Peptides; Sequence Analysis, Protein; Spectrometry, Mass, Electrospray Ionization; Wasp Venoms; Wasps